A review on the antimicrobial and antibiofilm activity of doped hydroxyapatite and its composites for biomedical applications. (June 2022) - Ghosh, Rupita; Das, Subhadip; Mallick, Sarada Prasanna; Beyene, Zerihun
Abstract: Hydroxyapatite is known as a bioactive, biocompatible, and osteoconductive material chemically similar to the mineral component of bone and teeth. Nano-hydroxyapatite has also drawn great concern from researchers since they are widely applied as biomedical materials. It is used as bone fillers, bone tissue engineering scaffolds, bioactive coatings, etc. However, the application of hydroxyapatite as biomedical materials is influenced by implant-associated infectious diseases and biofilm formation on the surface of the implant. As a result, biofilm formation is one of the most serious complications of implant surgery, and it always leads to severe physiological damage and additional costly surgical procedures. Therefore, imparting antimicrobial and antibiofilm properties to these implants is very much necessary. In this respect, the present review covers the various aspects of implant-associated infection including the biofilm formation and the cause of the infection with some examples. The remedy of the infection will be highlighted in terms of the application of doped hydroxyapatite with various metal ions/oxides or its various composites. The relationship of various parameters like concentration of a given material, mole fraction of metal doping, post processing-treatment, etc. on the antimicrobial property of the doped composites has also been discussed to facilitate the remedial process. Graphical Abstract: ga1